Analysis of the Role of Vocational Education for the Halal Tourism Development in Indonesia - Fahmi Achta Pratama; M. Wahyudi; Doni Eka Putra; Mulyadi Muslim; Hansi Effendi (Edumaspul: Jurnal Pendidikan, 2023)
Halal tourism, a concept rooted in Islamic economics, holds significant potential within the global economic cycle. In Indonesia, the largest Islamic country, the prospects for the development of halal tourism are particularly promising. Vocational education is identified as a pivotal element in the efforts to cultivate the halal industry in Indonesia, playing a crucial role in this development. The research methodology employed for this study was based on library research. The stages encompassed selecting research topics, determining focal points, collecting literature reviews, preparing data presentations, and compiling the final report. A total of 12 articles published between 2010 and 2022 were analyzed, sourced from Google Scholar and Harzing via Publish or Perish, using keywords such as "peran pendidikan vokasi," ( the role of vocational education) "peran pendidikan vokasi dan pariwisata," (the role of vocational education and tourism) and "pengembangan pariwisata halal di Indonesia."(development of halal tourism in Indonesia). The study's findings emphasize the significant role played by vocational education in the development of halal tourism in Indonesia. Vocational education, with its focus on equipping graduates with both soft and hard skills, work experience, and entrepreneurial capabilities, emerges as a crucial factor in this context. In conclusion, this study underscores the vital contribution of vocational education to the growth of halal tourism in Indonesia. It not only fosters interest in halal tourism among graduates but also ensures their preparedness for roles in the field. Moreover, vocational education facilitates connections with halal tourism jobs, ultimately contributing to the expansion of the pool of skilled professionals in the halal tourism sector within Indonesia.